EVALUATION OF SEXUAL FUNCTION INPENILE FRACTURE SURGERY PATIENTS - AKHTAR, M; ULLAH, MS; ZAFAR, Z; KHAN, MU; USMAN, HM; LODHI, MHK (Biological and Clinical Sciences Research Journal, 2022)
To assess the effects of surgical treatment of penile fracture on sexual function including psychological effects due to this traumatic experience. A prospective study was carried out at Department of Urology in Ibne Sina Hospital & MMDC Multan September 2021-September 2022. A total of 20 men undergoing surgical treatment for penile fractures were selected for the study. A detailed physical examination was done and subjects were questioned about psychological sexual problems and erectile dysfunction, penile nodules and penile curvature post-surgery. The average age of study patients was 37 years with an age range of 18-65 years. Two patients (10%) reported penile curvature. Erectile dysfunction was recovered in 17 patients (85%), six months after the surgery. 15 patients (75%) developed a fear of future penile fracture. 13 patients (65%) changed their sexual habits like avoiding vigorous sexual intercourse. Surgical treatment of penile fractures can lead to various postoperative complications both physical and psychological but they develop late in time after surgery and patients should seek treatment for such complications.